Thermal Springs and Geothermal Energy in the Qinghai-Tibetan Plateau and the Surroundings - Liao, Zhijie (Springer Hydrogeology,, 2018)
This book introduces readers to the rich and varied thermal springs of the Tibetan Plateau, which is steadily rising due to the collision of two continental plates. Readers will discover a wealth of information on boiling springs and hot springs, including their location and elevation, temperature, geological characteristics, and water chemical data, as well as tables on warm and tepid springs. Shedding new light on this vital supplement to hydroelectric resources in remote southwest China, the book will appeal to a broad relationship, from experts researching the Tibetan Plateau to companies specializing in geothermal exploration.